Changing stocks, flows, and behaviors in industrial ecosystems - Ruth, Matthias; Davidsdottir, Brynhildur; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2008)
Industrial ecology provides a consistent material and energetic description of human production and consumption processes in the larger context of environmental and socioeconomic change. The contributors to this book offer methodologies for such descriptions, focusing on the dynamics associated with stocks of materials and capital, flows of raw materials, intermediate products, desired outputs and wastes, as well as the associated changes in behaviors of producers, consumers and institutions.
pt. 1. Background and concepts -- pt. 2. Stocks and flows dynamics -- pt. 3. Agent-based analysis of dynamic industrial ecosystems.
Includes bibliographical references and index.
Keywords: Consumption (Economics) -- Environmental aspects; Production (Economic theory) -- Environemntal aspects; Consumption (Economics) -- Social aspects; Production (Economic theory) -- Social aspects; Organizational sociology; Electronic books